2021
DOI: 10.1186/s12967-021-02903-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circRNA–miRNA–mRNA networks contributes to explore underlying pathogenesis and therapy strategy of gastric cancer

Abstract: Background Circular RNAs (circRNAs) are a new class of noncoding RNAs that have gained increased attention in human tumor research. However, the identification and function of circRNAs are largely unknown in the context of gastric cancer (GC). This study aims to identify novel circRNAs and determine their action networks in GC. Methods A comprehensive strategy of data mining, reverse transcription-quantitative polymerase chain reaction (RT-qPCR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 58 publications
(67 reference statements)
0
23
0
Order By: Relevance
“…By querying the protein interaction database and the associated literature, a protein interaction network was constructed ( Fig. 7 ) and 37 proteins with interactive associations were selected for further analysis ( Table V ) ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…By querying the protein interaction database and the associated literature, a protein interaction network was constructed ( Fig. 7 ) and 37 proteins with interactive associations were selected for further analysis ( Table V ) ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…This regulatory network helps classify histology, regulate disease progression, and explore strategies in GC. 13 , 14 , 15 For example, the hsa_circ_0004771 /miR‐149‐5p/AKT1/mTOR 16 and CircPDSS1 ( hsa_circ_0093398 )/miR‐186‐5p/NEK2 17 pathways have been shown to promote GC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Xiong et al found that hsa_circRNA_100291 and hsa_circRNA_104515 may function as ceRNAs to exert critical roles in HCC [12]. Dong et al uncovered six circRNAs (hsa_ circ_0000390, hsa_circ_0000615, hsa_circ_0001438, hsa_ circ_0002190, hsa_circ_0002449 and hsa_circ_0003120) that might function as ceRNA to play important roles in gastric cancer by establishing circRNA-miRNA-mRNA regulatory networks [13]. Bai et al predicted that 3 cir-cRNAs (hsa_circ_0029340, hsa_circ_0025135, hsa_ circ_0039238) were ascertained as ceRNA to regulate the expression of 6 miRNAs (miR-1205, miR-657, miR-587, miR-637, miR-1278, miR-548p) in clear cell renal cell carcinoma [14].…”
Section: Introductionmentioning
confidence: 99%